(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Asthma, kidney and liver faliures, heart disorders, various types of cancer, infertility, oestoporesis, genetic disordersoxidastive stress, inflammation, rheumatoid arthritis, stroke, auto immune conditions, are just a few names taken in the long list of diseases caused by plastics. Somewhere down the line, there was lack of knowledge regarding these drastic effects of plastics and related additives on environment and human health and it was used extensively not knowing its effects on right from new born babies to adults. The general health and well-being of the entire world population is at stake due to the adverse effect of plastic. We need to alter many ways to ward off or reduce its negative impact. The present paper focuses on the health issues caused by plastics, its additives and components, so that our focus turns to take proper measures to reduce negative impacts of plastic on world human health.